2013
DOI: 10.1152/ajpheart.00906.2012
|View full text |Cite
|
Sign up to set email alerts
|

The second member of transient receptor potential-melastatin channel family protects hearts from ischemia-reperfusion injury

Abstract: The second member of the transient receptor potential-melastatin channel family (TRPM2) is expressed in the heart and vasculature. TRPM2 channels were expressed in the sarcolemma and transverse tubules of adult left ventricular (LV) myocytes. Cardiac TRPM2 channels were functional since activation with H2O2 resulted in Ca(2+) influx that was dependent on extracellular Ca(2+), was significantly higher in wild-type (WT) myocytes compared with TRPM2 knockout (KO) myocytes, and inhibited by clotrimazole in WT myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
106
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 51 publications
3
106
1
Order By: Relevance
“…Number 11 November 2014 present study, Miller et al (43) found that an absence of TRPM2 exacerbated myocardial ischemic injury and increased oxidative stress, whereas we found a reduction in both ischemic injury and oxidative stress in the kidney. The reasons underlying the differential responses to coronary versus kidney ischemia in the same Trpm2-KO mouse are not clear but may relate to different functions for ion channels and intracellular calcium regulation in epithelia and excitable tissues.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Number 11 November 2014 present study, Miller et al (43) found that an absence of TRPM2 exacerbated myocardial ischemic injury and increased oxidative stress, whereas we found a reduction in both ischemic injury and oxidative stress in the kidney. The reasons underlying the differential responses to coronary versus kidney ischemia in the same Trpm2-KO mouse are not clear but may relate to different functions for ion channels and intracellular calcium regulation in epithelia and excitable tissues.…”
Section: Discussioncontrasting
confidence: 50%
“…Conversely, TRPM2 is inhibited by low temperature and acidosis, both of which reduce ischemic AKI (46,47). We explored the role of TRPM2 in AKI in vivo using a newly developed Trpm2-KO mouse (43). Our studies yielded several important findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To form a functional channel, Trp proteins assemble into either homo-or heterotetramers, with the putative pore formed by loops between the fifth and sixth TM domains (21,23). The Trp-melastatin (Trpm) subfamily consists of eight mammalian members (Trpm1-Trpm8) (30), of which Trpm2 (27), -m4, -m5, and -m6 (49) are expressed in the heart. Although Trpm4 is associated with conduction abnormalities and cardiac arrhythmias (1,36), there is little information on the physiological and pathophysiological function of Trpm2 in the heart.…”
mentioning
confidence: 99%
“…Trpm2 is expressed in the sarcolemma and transverse (t) tubules in adult mouse ventricular myocytes (27). In adult cardiac myocytes, Trpm2 is activated by H 2 O 2 and intracellular adenosine diphosphate-ribose (ADPR), inhibited by clotrimazole and flufenamic acid, does not inactivate, and has a conductance for Ca 2ϩ that is ϳ50% of Na ϩ (26,27).…”
mentioning
confidence: 99%